Analysis of influencing factors for the realization of the ecological product value in national forest parks based on intuitionistic fuzzy DEMATEL-ISM - Hanjie, Xiao; Hongxia, Zhong; Qianhui, Bao; Yingnuo, Dong; Qiang, Zhu (Frontiers in Environmental Science, 2025)
Identifying the influencing factors and specific feasible paths for realizing the ecological product value of national forest parks, along with transforming the potential ecological value of ecological products into economic and social benefits, is a practical issue for achieving the transformation of “two mountains” and promoting common prosperity. In this paper, we take the Qianjiangyuan National Forest Park as the object of analysis, based on the theory of supply and demand; analyze the supply and demand mechanism for the realization of the ecological product value from three stages: supply, transformation, and demand; and summarize the influencing factors of the realization of the ecological product value in the national forest park. On this basis, we construct the intuitionistic fuzzy DEMATEL-ISM model and adopt the MICMAC method to clarify the hierarchical relationship and correlation among factors, and determine the key factors affecting the realization of the ecological product value in national forest parks. The results show that the top three factors of influence degree and centrality degree are technical support, definition of ecological resource property rights, and ecological industrialization, which have greater contribution and importance to the system. Among them, technical support is a key factor, and digital technology empowerment provides a power source for realizing the value of ecological products in national forest parks.